2019
DOI: 10.1002/app.47934
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical property and structure of a butadiene rubber composite filled with syndiotactic polybutadiene resin

Abstract: To obtain a novel resin‐reinforced elastomer, a butadiene rubber composite filled with syndiotactic polybutadiene (SPB) resin [vinyl cis rubber (VCR)] is designed. The VCR is synthesized by two‐step polymerization of 1,3‐butadiene in one pot. The SPB fibril is highly dispersed in a 1,4‐cis polybutadiene rubber (BR) matrix. Increasing the SPB content improves the tensile strength of the VCR. The nanostructure of the VCR is investigated by using a nano‐palpation atomic force microscope. The interfacial region be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…While increasing the content of inorganic filler leads to more pronounced reinforcing effects in vulcanized rubber compounds, it can also lead to unwanted increases in tire mass and hysteresis [ 20 , 21 , 22 ]. As an alternative to inorganic fillers, the tire industry explored a broad range of lower density polymeric fillers in rubber compositions [ 23 ], leading to reductions in tires mass and rolling resistance [ 24 ]. Many different polymers, including polystyrene [ 25 ], syndiotactic polystyrene [ 26 ], poly(methyl methacrylate) [ 27 ], isotactic polypropylene [ 28 , 29 ], polyurethanes, poly(ethylene terephthalate) [ 30 ], polyamides [ 31 , 32 ], polycarbonates [ 33 ], syndiotactic polybutadiene (PBD) [ 21 , 22 , 34 ], ultra-high-molecular-weight polyethylene (UHMWPE) [ 35 , 36 , 37 ] and poly(alkyl methacrylate)s [ 38 ], were studied as thermoplastic fillers to improve the properties of rubber compositions ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…While increasing the content of inorganic filler leads to more pronounced reinforcing effects in vulcanized rubber compounds, it can also lead to unwanted increases in tire mass and hysteresis [ 20 , 21 , 22 ]. As an alternative to inorganic fillers, the tire industry explored a broad range of lower density polymeric fillers in rubber compositions [ 23 ], leading to reductions in tires mass and rolling resistance [ 24 ]. Many different polymers, including polystyrene [ 25 ], syndiotactic polystyrene [ 26 ], poly(methyl methacrylate) [ 27 ], isotactic polypropylene [ 28 , 29 ], polyurethanes, poly(ethylene terephthalate) [ 30 ], polyamides [ 31 , 32 ], polycarbonates [ 33 ], syndiotactic polybutadiene (PBD) [ 21 , 22 , 34 ], ultra-high-molecular-weight polyethylene (UHMWPE) [ 35 , 36 , 37 ] and poly(alkyl methacrylate)s [ 38 ], were studied as thermoplastic fillers to improve the properties of rubber compositions ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Due to its unique mechanical properties that originate from the combination of properties of plastic and rubber, sPB reveals a wide range of applications in the elds of bres, lms, moulded articles, and recently has been used as synthetic rubber reinforcing llers. [8][9][10][11][12] Despite this, the inherent shortfall of low surface energy makes sPB display inferior properties with respect to adhesion, toughness, paintability, miscibility and rheological properties. Improving the hydrophilicity and developing functionalized sPB has been the long-term pursuit for scientists.…”
Section: Introductionmentioning
confidence: 99%
“…-ray spectra of the resultant copolymer products (runs11,13,16). DSC curves of the resultant copolymer products (runs[11][12][13][14][15][16].This journal is © The Royal Society of Chemistry 2019 RSC Adv., 2019, 9, 33465-33471 | 33469 Paper RSC Advances Open Access Article. Published on 17 October 2019.…”
mentioning
confidence: 99%
“…Sidewall should also provide superior resistance of crack growth over long time at smaller strains experienced during regular use. In addition, sidewall must withstand both types of crack growth over a broad span of temperatures and after aging for many years 7 . An ultra‐low hysteresis tire should have a low heat generating sidewall with superior cut or crack growth resistance along with weathering resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Syndiotactic polybutadiene (SPB) having 99.3% 1, 2‐configuration & with 99.1% syndiotacticity also behaves as a thermoplastic 12 . With the presence of the same monomer unit in both BR and SPB, superb compatibility between them provides a highly dispersed SPB fibril cohering strongly to BR throughout the interface and successfully reinforces the matrix 7 . Pan and co‐workers have shown that SPB can effectively reinforce the rubber matrix even in absence of reinforcing fillers 13 .…”
Section: Introductionmentioning
confidence: 99%